The Role of The School Principal in Increasing The Quality of Education in Vocational schools (Universitas PGRI Sumatera Barat, 2023)
Based on Regulation of the Minister of Education, Culture, Research and Technology number 40 of 2021 about teacher assignment as head school have task tree managerial, development entrepreneurship, and supervision to teachers and staff education. Study This aim For describe (1) how role head school as manager in increase quality education (2) how role head school as developer entrepreneurship (3) how role head school as internal supervisor increase education quality. Type research is descriptive qualitative naturalistic with use technique data collection in the form of interview, observation, and documentation. Results obtained from study This are (1) role head school as manager in increase education quality (2) role head school as developer entrepreneurship in increase education quality (3) how role head school as internal supervisor increase education quality. For avoid error in study this, then done testing data validity with discussion colleagues, data triangulation, and triangulation data source. Then the data is analyzed with use data analysis ie data reduction, data presentation and conclusion. Research results This can concluded role head school in increase education quality as (1) manager, (2) developer entrepreneurship, and (3) supervisors.